Entre Techniques et Stratégies D’enseignement Dans L’université Algérienne - Abada, Rofia (Finance and Business Economies Review, 2018)
Two important values that the Algerian University must ensure are Excellence and Accessibility. It must respond to several challenges that continue to increase over the years, in the face of globalization and financial globalization, and also in the face of a digital era that is booming. Finally, higher education must translate the pedagogical vision and this requires revisiting the ways in which training programmes are designed and taught, as well as evaluating student learning. Methodological tools are needed to make these pedagogical and academic practices effective and above all consistent with the institutional requirements and national programmes set by the Algerian University. Contemporary higher education, therefore, is designed through high-level educational planning, teaching methods and techniques that are appropriate and especially that follow the movement of the digital era, support systems are mandatory or even necessary, for students, as well as modalities of assessment of their achievements to meet the needs of the academic community in Algeria.